The Effect Of Lego Letters Media On Early Reading Ability In Children Ages 5-6 Years In Kindergarten Yasril Ananta Baharuddin Parepare City - trisnawaty, susi (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
Background : Early reading is defined as a process from written symbols (letters) into speech. Children who are often introduced to reading will get used to seeing books as a source of information. Lego as a constructive game in the form of building, organizing and managing various media around it has been commonly played by Early Childhood Children during their development. Objectives : How to describe the development of learning in children before and after using Lego media, how to describe early reading skills in children before and after using Lego media, and the effect of using Lego media on early reading skills. Method : The approach used in this study is a quantitative research approach, namely the research was conducted to analyze the effect of the experimental method on children's early reading abilities. The type of research used in this research is "Two Groups Pretest Posttest Design", which is a research design that has a pretest before being given treatment and a posttest after being given treatment. Results : The results of the Wilcoxon Signed Ranks test using the SPSS application obtained Asymp Sig (2-tailed) 0.05 <0.05, then H0 was rejected and H1 was accepted, meaning that there was an effect of playing lego letters on children's early reading abilities. This shows that the early reading skills of children who received the lego letter game treatment were better than children who received the treatment. Conclusion : Children's early reading ability before learning to use Lego media shows that some children do not yet have awareness of text messages, the alphabet and phonemics, do not yet have the basic skills needed to write, are not able to express questions and ideas and are able to use their language skills to work together. In the lego letter game to improve early reading skills, children experience improvement from each meeting so that there are differences in children's early reading development after research.